Ergonomic Assessment and Prevalence of Work-Related Musculoskeletal Disorders (WRMSDs) Among Administrative Clerical Staff in Tertiary Care Hospitals of Rawalpindi - Sair, Farrukh; Rathore, Mommana Ali; Butt, Muhammad Farhan; Mansoor, Eisha; Minallah, Asim (Pakistan Armed Forces Medical Journal, 2026)
Objective: To identify ergonomic factors contributing to work-related musculoskeletal disorders (WRMSDs) amongst clerical staff of tertiary care hospitals at Rawalpindi.Study design: Analytical cross-sectional.Place and Duration of study: Pak Emirates Military Hospital, Combined Military Hospital, Rawalpindi, Pakistan, from Sept to Dec 2024.Methodology: The study was conducted on 217 clerical staff of both genders aged 30-50 years. A self-structured questionnaire, comprising three sections, was used. The first part comprised demographic information, the second part consisted of questions regarding various factors contributing to musculoskeletal discomfort, and the third part ascertained whether the pain was work-related. Workstation risk assessment was done by the Rapid Office Strain Assessment (ROSA) tool. Data was analyzed using SPSS version 26.00. The chi-square test and Pearson correlation were applied to find an association between the ROSA high-risk category and WRMSDs.Results: A workstation assessment was done, and 138(63.88%) workstations were at risk. The major areas of complaint were neck pain 72(33.33%) and back pain 67(31.01%). Years of service, number of breaks, and duration of breaks were significantly associated with WRMSDs. A significant association (p=0.001) was seen between the ROSA risk category and the development of WRMSDs. A weak positive correlation (R2=0.059) was found between the ROSA grand score and the WRMSD score. Lumbar/cervical support usage was found among 76(50.3%) of the clerical staff having WRMSDs.Conclusion: Most administrative clerical staff with poor ergonomic setups and high ROSA scores had significant musculoskeletal discomfort, particularly neck (34%) and back pain (27.5%).